2013
DOI: 10.1002/aenm.201300396
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Application of Ferroelectric P(VDF‐TrFE) Nanoparticles in Organic Photovoltaic Devices for High Efficiency

Abstract: The power conversion effi ciency (PCE) of organic photovoltaic devices has entered the over 10% era. [ 1,2 ] Interlayers between the organic active layer and the electrodes play important roles in achieving high effi ciencies. Many types of interlayers have been reported, such as metal oxides, [3][4][5] polymer electrolytes, [ 6,7 ] and low-work-function metals. [ 8 ] Generally, these interlayers have the function of bridging the Fermi energy of the electrode and the energy levels of the organic semiconductor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 36 publications
2
53
1
Order By: Relevance
“…For the FE-OPV device with P(VDF-TrFE) at the organic/electrode interface, the generated electric eld is expected to be switched parallel or antiparallel with the built-in eld, resulting in better and worse device performance. 40,130,136 This was clearly demonstrated by Yuan et al as shown in Fig. 8a.…”
Section: Switchable Property Of Fe-opv Devicessupporting
confidence: 59%
See 2 more Smart Citations
“…For the FE-OPV device with P(VDF-TrFE) at the organic/electrode interface, the generated electric eld is expected to be switched parallel or antiparallel with the built-in eld, resulting in better and worse device performance. 40,130,136 This was clearly demonstrated by Yuan et al as shown in Fig. 8a.…”
Section: Switchable Property Of Fe-opv Devicessupporting
confidence: 59%
“…Ferroelectric polymers, such as P(VDF-TrFE), can be deposited by various methods including spin coating, 130 electrospinning, 131 nano-imprinting, 40,132,133 and Langmuir-Blodgett (LB) deposition. 70,75 The spin coating from a low boiling point solvent usually leads to an amorphous lm, which can be thermally annealed to increase its ferroelectric phase at a temperature higher than its Curie point.…”
Section: 129mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the resulting polymer nanoparticles are composed of the polymer without modifications in its molecular weight and chemical structure [21]. Although the nanoparticle preparation methods have been applied to a great variety of polymers, studies on ferroelectric polymer nanoparticles are relatively scarce [22]. The modification of some physical properties like the glass transition or the melting and crystallization behavior of polymer nanoparticles in comparison with the bulk behavior has been investigated for some polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Another class of useful ferroelectrics is polymers [19], most notably those based on vinylidene fluoride (VDF) [20,21]. Copolymers of VDF with trifluoroethylene (TrFE), P(VDF-TrFE), for example, have become the ferroelectric polymer of choice for applications, due in part to the variety of ways they can be prepared in bulk using inexpensive solution-processing methods [22] and can be formed into high-performance thin films and nanostructures [21,[23][24][25][26][27]. The ferroelectric polymers, however, have not proven particularly amenable to synthetic modification for optimizing ferroelectric properties in the way the ferroelectric oxides have [28].…”
Section: Introductionmentioning
confidence: 99%